Genetic intervention in pigs to control Salmonella shedding - Petry, Derek (Kansas State University, 2013)
Salmonellosis is one of the most important bacterial foodborne infections in the United States resulting in over 1 million illnesses and 375 deaths annually. Salmonella serotypes cause several types of disease in humans: gastroenteritis, enteric fever, septicemia, focal infections, and an asymptomatic carrier state. Salmonella-shedding pigs are known to constitute a risk factor for contamination of carcasses during the slaughter process. Vaccination has generally not been effective in the prevention of Salmonella, partially because of the rapid mutation rate. Previous research has indicated that >70% of farms tested in Iowa were positive for Salmonella during 2006-2009. Salmonella-colonized pigs are usually asymptomatic carriers of the bacterium and can shed upon exposure to stress causing contamination of pen-mates, trailers used for shipping, and lairage areas at processing facilities. Emergence and dissemination of antimicrobial-resistant pathogens, which antibiotics are commonly used in pig production, have become a public health concern worldwide. For this reason, alternative interventions need to be evaluated for effectiveness. The objective of this report was to determine if there is a genetic basis for host resistance or susceptibility to Salmonella through quantitative and/or molecular selection. Genetic improvement of disease resistance and/or tolerance in animals is a potentially effective intervention for addressing pre-harvest food safety issues. Previous research has demonstrated genetic control of the immune response to pathogens. Developing a strong innate response to infection, so the animal does not become ill or become a carrier, is the basis for a genetic intervention for Salmonella. Quantitative trait loci for humoral and innate immune response have been detected for E. coli through leucocyte counts, cytokine concentration, mitogen-induced proliferation, and levels of pre-infection antibody titers. Single nucleotide polymorphisms have been found and can be exploited for genetic improvement of the innate immune response in pigs when infected with Salmonella. Pigs that differentially express polymorphisms and persistently shed the bacteria versus pigs that do not shed or shed little can be used as criteria for selection when developing the intervention.
Keywords: Salmonella; Genetics; Pigs; Food Science (0359); Genetics (0369)